Fast cycle time : - Meyer, Christopher (Free Press, 1993)
Employing an ongoing case study, Core Products, Inc., throughout the text, Meyer shows how to redesign the organization for manufacturability and assembly, how to implement multifunctional teams that work, how to analyze and map critical cycle time interdependencies such as "co-location," and how to measure the impact of cycle time on business performance. Meyer's practical approach provides a simple methodology for organizations to deliver products to customers rapidly, accurately, and reliably. "Chris Meyer interrelates many pieces that we have all read about in different places into a coherent guide to making it happen.